2023
DOI: 10.1002/adhm.202300328
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Periodontal Ligament Transplantation Activated by Gold Nanoparticles Protects Alveolar Bone

Abstract: Stem cell therapy might be a promising method to stimulate alveolar bone regeneration, which is currently a major clinical challenge. However, its therapeutic features largely depend on pretreatment and transplantation preparation. Herein, a novel biomimetic periodontal ligament transplantation composed of human periodontal ligament stem cells (hPDLSCs) pretreated with gold nanocomplexes (AuNCs) and embedded in a type-I collagen hydrogel scaffold is developed to protect alveolar bone from resorption. AuNCs are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The AuNPs in Au@MPN-BMP2 exhibit several mechanisms to alleviate periodontal inflammatory bone loss. They can inhibit the polarization of macrophages toward the M1 phenotype during inflammation and enhance the expression of BMP2 in macrophages. , Additionally, AuNPs can induce periodontal tissue regeneration by enhancing the autophagy capability of periodontal ligament stem cells (PDLSCs) ,, and directly activate the p38 MAPK pathway to promote the osteogenic differentiation of PDLSCs . Masson and H&E staining of periodontal tissue revealed collagen loss and increased inflammation in the blank group.…”
Section: Resultsmentioning
confidence: 99%
“…The AuNPs in Au@MPN-BMP2 exhibit several mechanisms to alleviate periodontal inflammatory bone loss. They can inhibit the polarization of macrophages toward the M1 phenotype during inflammation and enhance the expression of BMP2 in macrophages. , Additionally, AuNPs can induce periodontal tissue regeneration by enhancing the autophagy capability of periodontal ligament stem cells (PDLSCs) ,, and directly activate the p38 MAPK pathway to promote the osteogenic differentiation of PDLSCs . Masson and H&E staining of periodontal tissue revealed collagen loss and increased inflammation in the blank group.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, in vivo cell labeling and tracking using AuNPs with CT have become a cost-effective and time-efficient approach [ 58 ]. Among the included studies, AuNPs have also been shown to have high potential in alveolar bone regeneration [ 13 , 59 , 60 ]. Besides the advantages mentioned above, AuNPs can promote the proliferation and differentiation of bone-forming cells, such as osteoblasts and mesenchymal stem cells [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nanomaterials, in the range of 1–100 nanometers, have gained significant attention in regeneration medicine due to their unique optical, mechanical, magnetic, electronic and catalytic properties [ 9 ], which explain their high biocompatibility, permeability, tunability and immune evasion capability. Hence, they exhibit tremendous potential in tissue engineering [ 10 ], as anti-bacterial agents [ 11 ], for drug delivery [ 12 ], tissue repair [ 13 ] and functional imaging (such as MRI and CT) [ 14 ]. Recently, various types of nanomaterials, such as nanoparticles, nanocapsules, nanocomposites, nanofibers, nanotubes and nanosheets, have achieved satisfying outcomes and could therefore be used to reconstruct structures and restore the functions of oral tissues [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Au-NPs, polydopamine, and transition-metal dichalcogenides have been combined with MBG for the photothermal treatment of bacterial infection and bone defect. However, compared with other photothermal materials, the small Au NPs can facilitate osteogenesis by activating related osteogenic protein. Therefore, the combination of Au NPs and MBG is a feasible approach to combine the advantages of both Au NPs and MBG that may inhibit bacterial growth and promote bone tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%